Community Vigilantes in Metropolitan Kano 1985-2005 - Rasheed Olaniyi (IFRA-Nigeria, 2005)
Kano is a city where a multi-layered form of community policing was established in the era of the rollback of the state in social provisioning in the midst of ever-increasing armed banditry and crime. Between 1985 and 2005, vigilante groups were established in almost all the neighbourhoods of Kano with the support of the traditional authority and community leaders. However, government interference, political instrumentalisation and inadequate support undermined its critical rote. Part of the ...